Brain Abscess due to Streptococcus Anginosus Secondary to Congenital Heart Disease in a Child - Khan, Ejaz Ahmed; Rafiq, Humaira; Usman, Muhammad (Infectious Diseases Journal of Pakistan, 2023)
Brain abscess in children is a life threatening infection. We are reporting a rare case of brain abscess caused by Streptococcus anginosus in an eight-year-old child who presented with fever, headache, vomiting and neurological symptoms. On detailed investigations she was found to have congenital heart disease as predisposing factor. She was treated with surgery and intravenous antibiotics and revealed a good outcome with no neurological deficit.